2017
DOI: 10.1021/acs.energyfuels.6b02343
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Energy Storage: Kinetic Investigations of the CuO/Cu2O Reaction Cycle

Abstract: Thermochemical energy storage (TCES) is considered a possibility to enhance the energy utilization efficiency of various processes. One promising field is the application of thermochemical redox systems in combination with concentrated solar power (CSP). There, reactions of metal oxides are in the focus of research, because they allow for an increase in the process temperature. The reaction system CuO/Cu2O has been reported as a suitable candidate for TCES. For proper development and modeling of combined CSP–T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 38 publications
2
30
1
Order By: Relevance
“…are important parts of solid oxide fuel cells. [32][33][34][35] To estimate the catalytic activity of Pt 3 Zr, we compare the oxygen doped formation energy between Pt 3 Zr and many metals. As shown in Fig.…”
Section: Structural Predictionmentioning
confidence: 99%
“…are important parts of solid oxide fuel cells. [32][33][34][35] To estimate the catalytic activity of Pt 3 Zr, we compare the oxygen doped formation energy between Pt 3 Zr and many metals. As shown in Fig.…”
Section: Structural Predictionmentioning
confidence: 99%
“…Unusual Arrhenius trends at high temperatures were observed and reported by Kyaw et al [64] in their study "Carbonation of CaO for High Temperature Thermal Energy Storage" and by Schaube et al [65] for the CaO/Ca(OH) 2 system at high H 2 O partial pressures. Deutsch et al found a negative activation energy for the CuO/Cu 2 O system in STA experiments [33].…”
Section: Model Id Type F(α) A1mentioning
confidence: 99%
“…Implementation of the those kinetics investigations in thermochemical energy storage would not be possible due to the impact of support materials on the kinetics of Cu2O/CuO, which should be studied separately. In thermochemical energy storage, the kinetics of the reduction of CuO to Cu2O was reported by Deutsch et al [33] in simultaneous thermal analysis (STA) and in a fixed-bed reactor. They indicated cycle stability of Cu2O/CuO system up to 20 cycles at 950 °C and at an oxygen partial pressure of 0.21 bar for the oxidation reactions, reduction was carried out in a nitrogen atmosphere.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations